Science Process Skills and Its Implementation in the Process of Science Learning Evaluation in Schools - Atik Kurniawati (Universitas Negeri Yogyakarta, 2021)
The study aimed to find out the science process skills and its implementation in the process of science learning evaluation in the schools. The studied aspects in the study consisted of the nature of science process skills, types of science process skills, assessment techniques for science process skills, and the assessment implementation of science process skills in learning in the schools. The research used a literature study containing relevant theories and further elaborated and its implementation in science learning in the schools. The study emphasized that science process skills were closely related to science learning and prioritize the overall assessment following the nature of science, such as product, process, and attitude dimensions. Those were covered in basic and integrated process skills. The most possible evaluation technique in measuring the science process skills was by observation or performance and written questions following the indicators of science process skills.